Analysis of the Morphology and Secondary Metabolite Content of Several Katuk (Sauropus androgynus) Accessions - Hakiki, Firdha Annisa; Masruroh, Qibtiyatul; Kartika, Juang Gema; Susila, Anas Dinurrohman; Kyoung, Cheong Min; Rahmah, Yulia (Department of Agronomy and Horticulture, IPB University, 2025)
Katuk (Sauropus androgynus) is a species valued for its nutritional and medicinal properties, as well as its potential applications in food, herbal medicine, livestock feed, and cosmetics. This study aimed to evaluate the morphological diversity and secondary metabolite profiles of four katuk accessions. Two analyses were conducted: (1) morphological characterization using cluster analysis and (2) qualitative and quantitative assessment of secondary metabolites. Cluster analysis revealed that all accessions showed high similarity with the “Paris”, an accession widely grown in West Java, Indonesia (similarity coefficient = 1.00), and moderate similarity with accessions “K1”, “K2”, “K4”, “Bastar”, and “Zanzibar” (distance coefficient = 0.68). Metabolite profiling indicated variations in compound abundance among accessions. “Ciaruteun Ilir 1” exhibited the highest vitamin E content; “Ciaruteun Ilir 2” had the highest fatty acid and phenolic content; “Pager Jangkung 1” accumulated the most flavonoids, while “Pager Jangkung 2” contained the most terpenoids and carboxylic acids. The leaves of katuk accessions in this study contains 14-17% squalene; this is an important finding for the pharmaceutical and health industries.